Evaluasi Corporate Governance pada Koperasi Serba Usaha (Studi Kasus: KSU Harapan Bersama) - Nurul Mahmudah; Ghea Dwi Rahmadiane (Monex: Journal of Accounting Research, 2023)
This study aims to evaluate the implementation of corporate governance in multi-purpose cooperatives. This study uses primary data and secondary data. Primary data was obtained from field surveys by distributing questionnaires to respondents, while secondary data was obtained from various publication sources. Data analysis uses frequency distribution to classify statements or statements from respondents on matters relating to the implementation of corporate governance from three aspects, namely organizational and management accountability, business accountability and member services, financial accountability. The results of the analysis in this study showed that the organizational and management accountability aspects of a total of 11 indicators stated that 9 indicators implemented properly and completely while 2 indicators had not implemented properly and completely. The aspect of business accountability and member service states that out of a total of 13 aspects, 9 indicators have been implemented properly and completely, while 4 indicators have not been implemented properly and completely. From a total of 10 indicators, there are 7 aspects of financial accountability that are implemented properly and completely, 2 indicators have not been implemented properly and completely, while 1 indicator has not been implemented  at all.